Prevalence and determinants of hypertension in elderly population of Raipur city, Chhattisgarh - Alam, Md. Naushad; Soni, Gopal Prasad; Jain, Kamlesh Kumar; Verma, Smita; Panda, Prem S. (International Journal of Research in Medical Sciences, 2017)
Background: Demographic transition across globe leading towards greying of population. Worldwide, raised blood pressure is estimated to cause 12.8% of the total annual deaths. This account for 3.7% of total DALYs. Several community-based studies have served to emphasize that hypertension is rapidly emerging as a major public health problem. However, only a few of these studies included elderly people. The objectives of the present study were to evaluate the prevalence and factors influencing hypertension among elderly population of Raipur city. Methods: This community based cross-sectional study was carried out in capital of Chhattisgarh, including urban and slum area from July 2013 to June 2014. Multistage simple random sampling methods were used. Study population comprises of all elderly 60 years and above residing in the study area for at least one year. A total of 640 subjects were included in study. Results: The overall prevalence of hypertension in present study was 50%, prevalent among females (55.49%), shows a significant positive association with body mass index, physical activity and age up to old age group (75-84) yrs. Surprisingly inverse association was observed with alcohol (P <0.001) and smoking (P <0.05) status. Conclusion: Our findings emphasize the public health importance of hypertension in the elderly in Raipur city, and need to strengthen the national programme for hypertension. From a public health perspective, there is definite need for screening of elderly.